New Baseband Radio Channel Impulse Processing Algorithms - Wieser, W.; Majer, N.; Haring, J. (Elektronika ir Elektrotechnika, 2009)
The method for radio channel pulse response processing with baseband conversion by six-port reflectometer technique is described. The received signal is converted by baseband conversion, digitized and the pulse response of radio channel is processed by proposed algorithms. These algorithms are working in real time and are able to estimate the amplitude, phase and delay of the received signal in each of propagation paths. The most promising algorithm (Exponential Power Descend Algorithm) achieved recovery successfulness of all signal paths equal approximately 90 % for SNR = 2.5 dB. Ill. 9, bibl. 11 (in English; summaries in English, Russian and Lithuanian).